Association between higher estimated glucose disposal rate and reduced prevalence of hyperuricemia and gout - Liu, Pengfei; Kadier, Kaisaierjiang; Wu, Xiaoli; Sun, Xiangyu; Zhang, Ge; Liu, Xiaozhu; Song, Daqing; Cui, Chunying (Frontiers in Nutrition, 2025)
ObjectiveInsulin resistance (IR) is closely associated with hyperuricemia (HUA) and gout; however, the relationship between the estimated glucose disposal rate (eGDR), a novel comprehensive indicator of systemic IR, and the prevalence of HUA and gout in the general population remains unclear.MethodsThis study analyzed data from 29,340 participants included in the National Health and Nutrition Examination Survey (NHANES) database. Multivariable logistic regression models and restricted cubic splines were employed to assess the association between eGDR and HUA and gout. Subgroup analyses were conducted to examine potential variations in the findings across different subgroups stratified by age, sex, race, and diabetes status.ResultsThe prevalence rates of HUA and gout among participants were 17.51 and 3.95%, respectively. Fully adjusted multivariable logistic regression models revealed that for each 1-unit increase in eGDR, the prevalence of HUA decreased by 17% (OR: 0.83, 95% CI: 0.81–0.85, p < 0.001), and the prevalence of gout also decreased by 17% (OR: 0.83, 95% CI: 0.79–0.87, p < 0.001). Compared to participants with eGDR < 4 mg/kg/min, those with eGDR levels of 4–6, 6–8, and > 8 mg/kg/min exhibited significantly lower OR values for both HUA and gout. Furthermore, subgroup analyses for HUA demonstrated significant interaction effects between eGDR and age, sex, race, and diabetes status (p < 0.05), while subgroup analyses for gout indicated significant interactions between eGDR and age and diabetes status (p < 0.05).ConclusionA significant inverse association was observed between eGDR and the prevalence of HUA and gout. Maintaining higher levels of eGDR plays a positive role in reducing the risk of HUA and gout in the general population. Moreover, this association was particularly pronounced in middle-aged and younger populations as well as in non-diabetic individuals.